Method for producing cubic lithium manganate particles

A thermal decomposition method using wurtzite-type MnO nanoparticles produces cubic LiMnO nanoparticles with controlled sizes under mild conditions, addressing the challenges of high-pressure and high-temperature requirements in existing methods, and enhancing battery performance through a hollow structure.

JP7609365B2Active Publication Date: 2025-01-07STANLEY ELECTRIC CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2020141544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-25
Publication Date
2025-01-07
Estimated Expiration
2040-08-25

AI Technical Summary

Technical Problem

Existing methods for producing cubic lithium manganate nanoparticles require high temperature and pressure conditions, long reaction times, and mechanical milling, making it difficult to control particle size and resulting in particles larger than 100 nm with mixed micro-order sizes.

Method used

A method involving thermal decomposition of manganese oxide and lithium amide in an inert atmosphere, using wurtzite-type MnO nanoparticles as a raw material, allows for the production of cubic LiMnO nanoparticles with controlled particle sizes of 100 nm or less, potentially hollow, without the need for high-pressure or high-temperature equipment.

Benefits of technology

Enables the production of cubic LiMnO nanoparticles under mild conditions, improving charging and discharging characteristics of lithium batteries by incorporating inclusions in the hollow structure, enhancing cathode material and battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609365000001
    Figure 0007609365000001
  • Figure 0007609365000002
    Figure 0007609365000002
  • Figure 0007609365000003
    Figure 0007609365000003
Patent Text Reader

Abstract

To produce cubic LiMnO2 nanoparticles without requiring special synthesis conditions or treatment and without the incorporation of coarse particles.SOLUTION: A method for producing LiMnO2 comprises a step in which an organic solvent, manganese oxide nanoparticles, and lithium amides are added to a reaction vessel and heated under an inert atmosphere to produce cubic LiMnO2 nanoparticles, and a step in which the produced particles are washed and recovered. Wurtzite MnO nanoparticles are preferably used as the manganese oxide, so that the LiMnO2 nanoparticles with a particle size almost equivalent to the wurtzite MnO nanoparticles of the Mn raw material is obtained. Furthermore, by controlling the reaction temperature, nanoparticles having a hollow structure can be formed.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to nanoparticles of an alkali metal manganate, such as lithium manganate, and in particular to cubic LiMnO2 nanoparticles. [Background technology]

[0002] Lithium manganate is a material that has attracted attention as a positive electrode material for lithium-ion batteries, and several materials have been developed with different ratios of Li, Mn, and O, such as LiMn2O4, LiMnO3, and LiMnO2. In addition, since the properties of the positive electrode material, such as the initial discharge capacity and charge / discharge characteristics, also depend on the crystal structure of the positive electrode material, various manufacturing methods and treatments for obtaining the desired crystal structure have been proposed.

[0003] Regarding LiMnO2, for example, Non-Patent Document 1 discloses a method of obtaining cubic LiMnO2 nanoparticles by mechanical milling orthorhombic LiMnO2. In this method, a mixture of Li2CO3 and Mn2O3 is first heated at 900°C in an inert atmosphere and synthesized to obtain bulk orthorhombic LiMnO2 as a precursor. The obtained precursor is then pulverized and refined by mechanical milling to obtain the desired cubic nanoparticles. It is believed that the obtained particles are a mixture of a wide range of particles, from a few μ order to tens of nm.

[0004] Also, Non-Patent Document 2 reports the synthesis of cubic LiMnO2 by a high-pressure synthesis method. In this method, Li2O and Mn2O3 are mixed and synthesized in a gold capsule under ultra-high pressure and high temperature conditions of 4.5 GPa and 1000°C, and the powder obtained as a mixture of Li2O and LiMnO2 is treated with water to finally recover single-phase cubic LiMnO2. [Prior art documents] [Non-patent literature]

[0005] [Non-Patent Document 1] Journal of Materials Chemistry A 2018, 6, 13943, Takahiko Sato, et al [Non-Patent Document 2] NEDO Report: April 2012 "Development of high-performance battery systems for next-generation automobiles / Next-generation technology development / Material design of next-generation high-capacity oxide cathode materials using high-pressure synthesis method" p. 26 Summary of the Invention [Problem to be solved by the invention]

[0006] In the method described in Non-Patent Document 1, high-temperature and long-term processing is required to obtain bulk LiMnO2, which is the starting material for obtaining cubic nanoparticles, and further high-temperature and long-term reactions are required to react the precursors with each other. In addition, long-term mechanical milling is required to obtain nanosized particles, but it is difficult to control the particle size with mechanical milling, and the obtained particles are mixed with micro-order particles, making it difficult to obtain particles with an average particle size of 100 nm or less.

[0007] The method described in Non-Patent Document 2 treats a smaller number of compounds than the technique in Non-Patent Document 1, but since the synthesis is performed under extremely high pressure and high temperature of 4.5 GPa, equipment compatible with high pressure and high temperature conditions is required.

[0008] An object of the present invention is to provide a method for producing cubic alkali metal manganate nanoparticles, particularly cubic LiMnO2 nanoparticles, without requiring special synthesis conditions or treatments and without the inclusion of coarse particles. [Means for solving the problem]

[0009] The method for producing alkali metal manganate nanoparticles of the present invention, which solves the above problems, includes the steps of adding an organic solvent, manganese oxide nanoparticles, and lithium amide to a reaction vessel, heating under an inert atmosphere to generate cubic alkali metal manganate nanoparticles, and washing and recovering the generated particles. In the method for producing LiMnO2 of the present invention, wurtzite MnO nanoparticles are preferably used as a raw material.

[0010] The cubic LiMnO2 of the present invention is characterized in that it is LiMnO2 produced by thermal synthesis, has an average particle size of 100 nm or less, and has a hollow structure. Effect of the Invention

[0011] According to the present invention, it is possible to provide alkali metal manganate nanoparticles, represented by cubic LiMnO2, without requiring additional treatment such as special reaction equipment or mechanical milling. The cubic LiMnO2 of the present invention has a hollow structure, and when used as a lithium battery material, the charge / discharge characteristics can be improved by adding an inclusion to the hollow portion, and the life of the positive electrode material and therefore the life of the lithium battery can be improved. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram showing an outline of a method for producing LiMnO2 according to the present invention. [Diagram 2] FIG. 2 shows X-ray diffraction (XRD) patterns of the particles obtained in Examples 1 and 2. [Diagram 3] 3A to 3C are transmission electron microscope images of the particles obtained in Example 1 and Example 2, and the MnO particles used as a raw material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, an embodiment of the method for producing a cubic alkali metal manganate of the present invention will be described. Here, a method for producing nanoparticles of LiMnO2, which is a typical alkali metal manganate, will be described.

[0014] The manufacturing method of the present invention is based on synthesis by a pyrolysis method, and includes the steps of preparing a Mn raw material, putting the Mn raw material, Li raw material, and a solvent into a reaction vessel, heating the vessel to a predetermined temperature of 350°C or less and reacting for a predetermined time (about 60 minutes), and recovering particles from the reaction liquid, as shown in Figure 1. Each step is described in detail below.

[0015] <Process 1> In the manufacturing method of the present invention, manganese oxide (MnO) nanoparticles and Li complexes such as lithium amide (LiNH2) are used as raw materials. The new combination of manganese oxide and lithium amide does not require high pressure, high temperatures of 1000°C, or long reactions, and cubic LiMnO2 can be produced by a reaction using a normal thermal decomposition method. In particular, by using wurtzite nanoparticles as manganese oxide, it is easy to obtain cubic crystals and to control the particle size.

[0016] Generally, the stable crystal structure of MnO is rock salt type, but it is known that MnO theoretically has a wurtzite type crystal structure, and although there are several production examples, no method is known for stably obtaining only wurtzite type MnO nanoparticles by synthesis. The applicant has developed and proposed a method for producing wurtzite type MnO nanoparticles by pyrolysis synthesis (Patent Application No. 2019-205644). In this method, a specific reducing agent is added to the reaction system to synthesize the nanoparticles, suppressing the generation of rock salt type MnO and layered double hydroxides as by-products, and wurtzite type MnO with a particle size of 100 nm or less can be stably obtained.

[0017] Specifically, when a manganese-containing compound is thermally decomposed to synthesize manganese oxide particles, a reducing agent consisting of at least one of a polyol-based material and an ethylene glycol stearate-based material, and preferably a particle size inhibitor, are added to the reaction system as additives. Then, the mixture is heated in a reduced pressure atmosphere (pressure of 1000 Pa or less, preferably 100 Pa or less) at a temperature of 200° C. or less, preferably 110 to 150° C., to form nuclei, and then heated to 225° C. to 275° C. in an inert gas atmosphere to grow the particles. By controlling the reaction time of this particle growth step, the size of the manganese oxide particles can be controlled to, for example, about 2 nm to 100 nm, preferably 30 nm or less. The average particle size can be, for example, 100 nm or less, more preferably 40 nm or less. After the particles are grown, the temperature is further increased to about 300° C. to mature the particles, thereby making the size uniform.

[0018] In the manufacturing method of the present invention, by using the wurtzite MnO nanoparticles (6 to 30 nm) prepared by the above-mentioned method as the Mn raw material, it is possible to obtain cubic LiMnO2 nanoparticles with a controlled particle size.

[0019] Li complexes such as LiNH2 and LiNR (R is hydrogen or an alkyl group) are used as Li raw materials. Among these, LiNH2, which has high activity, is particularly preferred. The Li source can be used in an equimolar amount to 100 times the molar amount of MnO, but it is preferable to use an excess amount relative to the stoichiometric ratio. By using an excess amount of LiNH2 (for example, 50 equivalents or more), LiMnO2 particles can be obtained stably.

[0020] As the solvent, an oxygen-containing organic solvent that serves as an oxygen source for LiMnO2 is used. As the oxygen-containing organic solvent, for example, ether solvents such as diphenyl ether, benzyl ether, and di-n-octyl ether can be suitably used, and diphenyl ether is particularly preferable.

[0021] <Process 2> The reaction is carried out under an inert gas atmosphere, so after the Mn raw material and the solvent are placed in the reaction vessel, the Li source (LiNH2) is placed in the reaction vessel in the inert gas atmosphere, and the reaction vessel is placed in a pressure-resistant vessel and sealed.

[0022] <Process 3> In an atmosphere of an inert gas such as nitrogen, the reaction temperature is heated to a reaction temperature (150 to 350°C in terms of heater temperature). The rate of temperature rise is preferably relatively slow, for example, about 5°C / min. After the reaction temperature is reached, the temperature is maintained for a predetermined time. The reaction is considered to proceed as follows. Below, the case where the Li source is LiNH2 will be explained. In this reaction, the reaction proceeds with wurtzite MnO nanoparticles as the starting material (nucleus), LiNH2 is coordinated to the particle surface, and the atoms in the MnO particles react with Li on the surface of the nanoparticles, forming LiMnO2 crystals. At that time, the metastable phase of the wurtzite crystal (arrangement of atoms) undergoes a crystal structure transformation to the stable phase of MnO2 phase by heating. On the other hand, the LiNH2 present in the system is active and easily decomposed at high temperatures in the presence of other materials, and serves as a source of Li. In this active state, Li is incorporated into the MnO crystal structure, and while incorporating oxygen in the solvent, a cubic LiMnO2 phase is formed.

[0023] Furthermore, when the reaction temperature is relatively high (for example, around 350°C), solid particles are obtained due to the high reaction rate. On the other hand, at a relatively low temperature (for example, 200°C), hollow particles are obtained. This is because, under low reaction temperature conditions, the growth rate of LiMnO2 is slow, and during this time, a sudden reaction is likely to occur at the contact points between active LiNH2 and MnO, and the atoms in the MnO nanoparticles move toward the LiNH2 coordinated to the surface of the MnO nanoparticles to react, causing the inside to become hollow and resulting in a hollow structure. In this way, the shape of the particles produced can be controlled by controlling the reaction temperature.

[0024] The reaction time is about 30 minutes to 2 hours. In the production method of the present invention, the reaction proceeds as described above, so that the synthesis is completed in a short time. After the reaction, the reaction vessel is quenched and removed from the pressure-resistant vessel.

[0025] <Step 4> The particles are collected from the reaction system in the same manner as in the general method for collecting metal oxides after synthesis, and are then repeatedly centrifuged using a solvent, washed, and collected.

[0026] The resulting particles are cubic LiMnO2 with an average particle size of 100 nm or less. By appropriately selecting the particle size of the MnO nanoparticles, the average particle size can be reduced to 40 nm or less. The shape can be solid or hollow. The average particle size referred to here is an average value calculated by measuring the particle sizes of 200 to 2000 particles using a transmission electron microscope.

[0027] According to the manufacturing method of the present invention, cubic LiMnO2, which could only be obtained by a production method requiring extremely high temperature, high pressure, and long time, can be obtained under mild conditions of 350℃ or less in a short time, and nanoparticles can be prepared without additional processing. In addition, since the particle size of cubic LiMnO2 nanoparticles depends on the size of the MnO nanoparticles, which is the starting material, it is possible to control the particle size of LiMnO2 nanoparticles, and the average particle size of the obtained particles is smaller than 100 nm.

[0028] In addition, depending on the reaction conditions, hollow-structured LiMnO2 nanoparticles can be formed. By creating a hollow structure, the density decreases, and by controlling the particle size and thickness, it is expected that the charge / discharge characteristics can be further improved and the weight can be reduced.

[0029] The method for producing cubic LiMnO2 of the present invention has been described above, but this method can also be applied to the synthesis of other alkali metal manganates such as NaMnO2. By replacing the Li source complex with, for example, a Na source, it is believed that it is possible to prepare NaMnO2 nanoparticles and their hollow structure nanoparticles, which are expected to be candidates for other electrode materials. EXAMPLES

[0030] Examples of the manufacturing method of the present invention will now be described.

[0031] <Example 1> [Preparation of MnO nanoparticles] 10 mL of oleylamine was used as the solvent, 1.5 mmol of manganese stearate (st-Mn) was used as the manganese material, 3.0 mmol of ethylene glycol (EG) was used as the reducing agent, 3.6 mmol of trioctylphosphine (TOP) was used as the coordinating agent, and 1.8 mmol of sulfur was used.

[0032] After filling the container (100 mL), the material was held at 70°C for 30 minutes in a nitrogen atmosphere, and then heated and held at 140°C for 2 hours in a reduced pressure atmosphere. The pressure at this time was about 100 Pa. The temperature was then raised to 250°C at a heating rate of 50°C / 5 minutes, and held at 250°C for 2 hours in a N2 atmosphere to grow crystals. The temperature was then further raised and held at 300°C for 15 minutes in a N2 atmosphere to perform crystal aging.

[0033] After cooling, 5 mL of hexane was added to the reaction solution, which was stirred and then collected in a centrifuge tube. Ethanol, a poor solvent, was added to flocculate the particles, which were then precipitated using a centrifuge. After discarding the supernatant, 5 mL of hexane was added and the particles were dispersed by stirring for 30 minutes on a shaker. Ethanol was added once more, and the same process was repeated once more to wash the particles, yielding MnO particles (red) with a particle size of 25 nm (particle size was confirmed by TEM).

[0034] [Synthesis of cubic LiMnO2] 0.14 mmol of the 25 nm MnO nanoparticles prepared as described above and 6 mL of diphenyl ether (liquid) as a solvent were added to a reaction vessel (100 mL), and then 10.8 mmol of LiNH2 (powder) was added to the reaction vessel under a N2 atmosphere, and the reaction vessel was placed in a pressure-resistant vessel and sealed. Under a N2 atmosphere, the heater temperature was increased at a rate of 5°C / min until it reached 350°C, and after reaching 350°C, the temperature was maintained for 60 minutes to complete the reaction. After that, the reaction vessel was rapidly cooled and removed from the pressure vessel.

[0035] 40 mL of ethanol was added to the reaction solution, and the centrifugal separation was repeated five times. The separated particles were then washed with ethanol and collected.

[0036] <Example 2> 0.14 mmol of 25 nm MnO nanoparticles prepared in the same manner as in Example 1, 10.8 mmol of LiNH2 (powder), and 6 mL of a solvent: diphenyl ether were added to a reaction vessel in the same manner as in Example 1, and the reaction was carried out under a N2 atmosphere. In this example, the mixture was heated to 200°C (heater temperature) at a temperature increase rate of 5°C / min and held at that temperature for 60 minutes. After the reaction, the mixture was rapidly cooled, centrifuged (5 times) and washed with ethanol in the same manner as in Example 1, and the particles were collected.

[0037] [Evaluation of collected particles] The particles recovered in Examples 1 and 2 and the MnO used as the raw material were analyzed by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The X-ray diffraction pattern is shown in FIG. 2, and the TEM images are shown in FIGS. 3(A) to 3(C). In FIG. 2, the bars shown under the diffraction pattern are the reference diffraction peaks, and the thick lines are the cubic LiMnO2 (COD 1514037 Li 0.5 Mn 0.5 The thin line indicates wurtzite-type MnO (COD 4117966 MnO). Figure 3 also shows a schematic diagram of the particle size and structure analyzed from a TEM image.

[0038] As shown in Figure 2, the particles of Example 1 and Example 2 both had peaks at positions that coincided with the peaks of the reference (cubic LiMnO2), confirming that the cubic LiMnO2 phase was formed. It was also confirmed that the raw material MnO was of the wurtzite type.

[0039] As shown in Fig. 3, the particle diameter of the obtained particles was smaller than 100 nm, generally 30 nm or less, in both Example 1 and Example 2. In addition, the TEM image confirmed that the average particle diameter was 19 nm in Example 1. In addition, the TEM image confirmed that a hollow structure was formed in Example 2, with the average particle diameter being 26 nm and the shell thickness being approximately 4 to 6 nm.

[0040] The particle size of the raw material MnO nanoparticles and the resulting LiMnO2 are almost the same, which is probably because Li enters the MnO nanoparticles during the reaction and the MnO particles dissolve due to the active LiNH2, which is generated by the high temperature treatment. To confirm this, the particle size of MnO particles was checked after treatment at 350°C without adding LiNH2, and no effect of this heat treatment on the particle size was confirmed.

[0041] Furthermore, when a reaction was carried out in the same manner as in Example 1 using MnO nanoparticles with a particle size different from the nanoparticles (25 nm) used in Example 1, it was confirmed that LiMnO2 with a particle size similar to that of the MnO nanoparticles used as the raw material was obtained.

Claims

1. A method for producing wurtzite manganese(II) oxide nanoparticles having a particle size of 100 nm or less, comprising: charging an oxygen-containing organic solvent, the wurtzite manganese(II) oxide nanoparticles, and a lithium complex into a reaction vessel; heating the oxygen-containing organic solvent, the wurtzite manganese(II) oxide nanoparticles and the lithium complex at a heating temperature of 150 to 350° C. under an inert gas atmosphere to produce cubic lithium manganate nanoparticles; and recovering the lithium manganate nanoparticles.

2. A method for producing lithium manganese oxide nanoparticles as described in claim 1, wherein the lithium complex is a lithium amide.

3. A method for producing lithium manganese oxide nanoparticles as described in claim 1 or 2, characterized in that the particle size of the wurtzite manganese oxide (II) nanoparticles is 30 nm or less.

4. A method for producing lithium manganese oxide nanoparticles described in any one of claims 1 to 3, wherein the heating temperature is lower than 200°C and the lithium manganese oxide nanoparticles are hollow.

Citation Information

Patent Citations

  • Positive electrode mixture with improved conductivity, positive electrode comprising the same, and electrochemical device

    JP2016524275A

  • Spinel-type lithium manganate and method for producing the same

    JP2020059622A